Main elements to be considered for the correct diagnosis of sarcopenia - José Hernández Rodríguez; Yuri Arnold Domínguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
The diagnosis of Sarcopenia is difficult because different researchers do not agree about the methods to be used and which cut-off points to set due to the complexity of the topic. It is evident that the use of practical, reliable criteria which are available to most of the researchers, will make it possible to diagnose this important gnoseological entity. For these reasons the objective of this work is to describe the main elements to take into consideration for the correct diagnosis of sarcopenia.It was used the Academic Google to look for information. The key words used were: sarcopenia, aging, muscular mass, muscular strength. Review and Research Articles and son Web pages were evaluated with less than ten years of publication, in Spanish, Portuguese or English which had an adequate methodological and scientific quality according the the author's criteria. Documents without these requirements were excluded. Tis allowed the study of 110 articles, from which 74 were referenced. It is concluded that to diagnose sarcopenia adequately it should be taken into consideration the clinical findings which indicate loss of muscular mass and strength, so as poor physical performance due to this condition. It will also depend on the definition used, measurable variables and the different cut-off points of lab tests used in relation with the characteristics of the studied population.